2022
DOI: 10.1038/s41531-022-00411-x
|View full text |Cite
|
Sign up to set email alerts
|

APOE E4 is associated with impaired self-declared cognition but not disease risk or age of onset in Nigerians with Parkinson’s disease

Abstract: The relationship between APOE polymorphisms and Parkinson’s disease (PD) in black Africans has not been previously investigated. We evaluated the association between APOE polymorphic variability and self-declared cognition in 1100 Nigerians with PD and 1097 age-matched healthy controls. Cognition in PD was assessed using the single item cognition question (item 1.1) of the MDS-UPDRS. APOE genotype and allele frequencies did not differ between PD and controls (p > 0.05). No allelic or genotypic association w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Particularly, numerous mutated genes, such as GBA 12,22,24 , LRRK2 [25][26][27] , PRKN 28,29 , PINK1 14,29 , and SNCA 27,30 have been demonstrated to modify the clinical heterogeneity of familial PD patients. In idiopathic PD, a number of genetic variants are found to be associated with the heterogeneity of clinical manifestations [31][32][33][34] . Yoshino et al (2022) identified 13 novel PRKN variants and revealed that patients with different PRKN variants showed heterogenous clinical features dependent on the number of alternate alleles 34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, numerous mutated genes, such as GBA 12,22,24 , LRRK2 [25][26][27] , PRKN 28,29 , PINK1 14,29 , and SNCA 27,30 have been demonstrated to modify the clinical heterogeneity of familial PD patients. In idiopathic PD, a number of genetic variants are found to be associated with the heterogeneity of clinical manifestations [31][32][33][34] . Yoshino et al (2022) identified 13 novel PRKN variants and revealed that patients with different PRKN variants showed heterogenous clinical features dependent on the number of alternate alleles 34 .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the motor function of idiopathic PD patients were associated with variants in SNCA 36,37 , BST1 38 , ATP8B2 39 , PARK16 40 , and APOE 41 . Additionally, variants of APOE 31,32 , SNCA 42 , TMEM106B 43 , COMT 44 , MAPT 23,44 , PICALM 45 have been found to be associated with variability of cognitive function in idiopathic PD patients. Nevertheless, the associations between genetic variations and clinical features in sporadic PD remain largely elusive and deserved to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…There have been only a few published studies exploring PD genetics in the African and African admixed populations, conducted with fewer than thirty samples in all instances 50,51,52,53,54 . In the present study, we have gathered the largest collection of PD patients and controls from African and African admixed ancestry populations to comprehensively assess the genetic architecture of PD on a genome-wide scale.…”
Section: Discussionmentioning
confidence: 99%
“…Published evidence has occasionally suggested that the presence of at least one APOE4 copy is related to earlier PD onset while the presence of APOE3 and/or APOE2 alleles may delay its onset [79][80][81][82][83]. At the same time, the vast majority of published reports failed to reproduce these associations precluding any relationship between APOE and age of PD onset [84][85][86][87][88][89].…”
Section: Clinical Links Between Apoe-pd and Pddmentioning
confidence: 99%